Respuesta :

pcai26

Answer:

see below

Step-by-step explanation:

17.

1/(-(-1/5))=1/(1/5)=5

apply point

-2=5(-2)+n

-2=-10+n

n=8

y=5x+8

18.

1/(-(2))=1/(-2)=-1/2

apply point

-1=-1/2(4)+n

-1=-2+n

n=1

y=-1/2x+1

19.

1/(-(3/4))=1/(-3/4)=-4/3

apply point

5=4/3(-3)+n

5=-4+n

n=9

y=-4/3x+9

20.

convert

x-4y=20

-4y=-x+20

y=1/4x-5

1/(-(1/4))=1/(-1/4)=-4

apply point

-5=-4(2)+n

-5=-8+n

n=3

y=-4x+3

21.

convert

5x-6y=18

-6y=-5x+18

y=5/6x-3

1/(-(5/6))=1/(-5/6)=-6/5

apply point

7=-6/5(10)+n

7=-12+n

n=19

y=-6/5x+19

22.

convert

6x+3y=-9

3y=-6x-9

y=-2x-3

1/(-(-2))=1/2

apply point

2=1/2(-2)+n

2=-1+n

n=3

y=1/2x+3